Comparison of Power Grip Strength in Male Knitter and Sedentary Worker - Tripti, Durratul Jahan; Kishwara, Segufta; Chowdhury, Mahfuza; Kawser, Tunajjina; Sumi, Sharmin Akhter; Mahmud, Shaila (Bangladesh Journal of Anatomy, 2024)
Context: The measurement of power grip strength is a simple and inexpensive method to assess hand functions. It is influenced by the health status and the level of occupational demand using hand. The study was carried out to compare the power grip strength of Bangladeshi male knitters and sedentary workers. Materials & Methods: A cross sectional analytical study was conducted in Dhaka Medical College, Dhaka from January 2017 to December 2017 on thirty three (33) adult Bangladeshi male sedentary workers (group A) and ninety nine (99) adult Bangladeshi male knitters (group B). Ninety nine participants of knitters were further subdivided into three subgroups according to their working experience in years. Hand grip strength dynamometer (Camry, USA) was used to measure the power grip strength. Results: Statistically significant difference (P<0.05) of mean power grip strength was observed between sedentary workers (group A) and knitters (group B) in both hands whereas the mean power grip strength was greater in the knitters than the sedentary workers. Among the knitters the more experienced subgroup had non-significantly higher (P<0.05) power grip strength than the less experienced subgroups. Conclusion: The present study showed that power grip strength was higher in male Bangladeshi knitters compared to sedentary workers in both hands. Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 1, pp. 22-25